Gesture of the teacher in the structure of external pedagogical technique - Щербина, Д. В. (Pedagogy of Higher and Secondary Education, 2012)
Shcherbyna D. V. Gesture of the teacher in the structure of external pedagogical technique. In the article the author considers the importance of teacher’s gesticulation in the outward structure of the pedagogical technique and analyzes the characteristics of its use in professional and pedagogical activities.